2018
DOI: 10.1515/znc-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Bacillus spp. from medicinal plants inhibit mycelial growth of Sclerotinia sclerotiorum and promote plant growth

Abstract: Plant growth-promoting bacteria that are also capable of suppressing plant pathogenic fungi play an important role in sustainable agriculture. There is a critical need for conducting research to discover, characterize and evaluate the efficacy of new strains of such bacteria in controlling highly aggressive plant pathogens. In this study, we isolated endophytic bacteria from medicinal plants of Bangladesh and evaluated their antagonistic capacity against an important phytopathogenic fungus Sclerotinia scleroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 80 publications
(81 reference statements)
1
10
0
Order By: Relevance
“…Past research on plant microbiomes has demonstrated growth-promoting effects ( Naik et al, 2019 ), the enhancement of plant resistance against pathogens ( Ansary et al, 2018 ; Vurukonda et al, 2018 ) and positive effects on overall plant fitness ( Rodriguez et al, 2009 ; Uroz et al, 2019 ). Further, implications of the microbiome on agricultural management ( Toju et al, 2018 ; Jones et al, 2019 ; Pacifico et al, 2019 ; Lyu et al, 2020 ), crop quality and postharvest processes ( Rillig et al, 2018 ) have been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Past research on plant microbiomes has demonstrated growth-promoting effects ( Naik et al, 2019 ), the enhancement of plant resistance against pathogens ( Ansary et al, 2018 ; Vurukonda et al, 2018 ) and positive effects on overall plant fitness ( Rodriguez et al, 2009 ; Uroz et al, 2019 ). Further, implications of the microbiome on agricultural management ( Toju et al, 2018 ; Jones et al, 2019 ; Pacifico et al, 2019 ; Lyu et al, 2020 ), crop quality and postharvest processes ( Rillig et al, 2018 ) have been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Citri (Huang et al, 2012), tomato bacterial wilt caused by Ralstonia solanacearum (Chen et al, 2013), and melon bacterial fruit blotch caused by Acidovorax citrulli (Fan et al, 2017). B. subtilis strains are the dominant endophytic bacteria associated with many plant species, and they commonly exhibit the ability to enhance host plant resistance to pathogenic fungi and bacteria (Ansary et al, 2018;Kushwaha et al, 2020;Xu et al, 2019Xu et al, , 2020. These B. subtilis also do not pose a risk to humans, making them ideal for use in biocontrol applications (Earl et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies demonstrating the suppression of Sclerotinia by Bacillus in vitro and exploring the mechanism of suppression (Li et al, 2009;Tonelli et al, 2010;Luduena et al, 2012;Figueredo et al, 2014;Vinodkumar et al, 2017;Ansary et al, 2018;Lopes et al, 2018;Massawe et al, 2018). The efficacy of Bacillus spp.…”
Section: Beneficial Bacteriamentioning
confidence: 99%